Repetition of the passed or new opportunities? Comments on Duntas L. New aspects of an old dilemma: treatment of hypothyroidism with L-thyroxine combined with L-triiodothyronine - Galina A. Melnichenko (Клиническая и экспериментальная тиреоидология, 2017)
This article is for comments and comprehensive discussion on relatively published review New aspects of an old dilemma: treatment of hypothyroidism with L-thyroxine combined with L-triiodothyronine by L. Duntas.